A Review On Flavonoids - Kumar, Hitesh; Chauhan, Ravi Singh; Kabra, M. P.; Bhandar, S. S. (Asian Journal of Pharmaceutical Research and Development, 2018)
Flavonoids are low molecular weight polyphenolic compound present in all vascular plants. They are primary recognised as the pigments responsible for autumnal burst hues and yellow, orange and red shades in flowers and fruits.Flavonoids have been show to possess a variety of biological activity at non-toxic concentration in living organism compelling data from various in vivo and invitro experimental. Several epidemiological studies have demonstrated the beneficial effect of dietary Flavonoids.They are ubiquitous in photosynthesis cells and are commonly found in fruits, nuts, seeds, tea, wine and honey.The mechanism of their cardio productive effect have been thought to stem from their free radical Scavenging antioxidant, antithrombotic, antiapoptopic and antihypertensive effect.